2015
DOI: 10.4238/2015.february.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic structure of mangaba remnants in states of northeastern Brazil

Abstract: ABSTRACT. In this study, we analyzed the genetic diversity and structure of remnants of mangaba populations in states of northeastern Brazil by applying 9 microsatellite markers previously developed to establish conservation strategies for germplasm and species preservation. Six to 20 individuals per population were analyzed, with a total of 94 individuals and 6 populations from the states of Ceará, Pernambuco, and Sergipe, Brazil. The intra-population positive fixation index (f) in all populations indicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
4
20
0
1
Order By: Relevance
“…Research on the mangaba tree is recent, especially the studies of genetic diversity using different molecular markers, such as RAPD [1] [2], ISSR [6] [7] [8] [9] and SSR [10]. These studies are important to assist in the knowledge of the genetic diversity of native populations and accessions, and can be used as tools to design conservation strategies and collection of new accessions to be introduced into the germplasm bank.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the mangaba tree is recent, especially the studies of genetic diversity using different molecular markers, such as RAPD [1] [2], ISSR [6] [7] [8] [9] and SSR [10]. These studies are important to assist in the knowledge of the genetic diversity of native populations and accessions, and can be used as tools to design conservation strategies and collection of new accessions to be introduced into the germplasm bank.…”
Section: Introductionmentioning
confidence: 99%
“…), who reported that there was great interpopulation genetic variability. However, Amorim et al (2015), using microsatellite markers in mangaba, observed greater variation within populations (83.18%) than between them (10.82%).…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, studies on the genetic diversity and structure of the remaining populations of mangaba are extremely important, in order to find alternatives for the species' preservation (Amorim et al, 2015). In addition, the domestication and incorporation of this species into production systems is directly related to knowledge of the range and distribution of genetic variability in natural populations (Costa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The divergence data were compared with previous successful studies in individuals of the native population of Hancornia speciosa Gomes (Santos et al, 2017;Silva et al, 2017;Soares et al, 2016;Amorim et al, 2015;Costa et al, 2015;Jimenez et al, 2015;Silva et al, 2013) and BAGs Costa et al, 2011;Luz, 2016;Vitória, 2017), with the use of molecular markers.…”
Section: Molecular Analysismentioning
confidence: 99%